2022
DOI: 10.21203/rs.3.rs-1564442/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Who and why: a study of British distrust in the government and media during the COVID-19 pandemic

Abstract: The COVID-19 pandemic represents a unique context for studying the spread of conspiratorial beliefs within the general population and their role in mediating compliance with government guidance. Here, we apply multivariate and machine learning methods to analyse data from tens of thousands of members of the British public at 6-monthly timepoints during the COVID-19 pandemic. We report that distrust and conspiratorial beliefs significantly predict non-compliant behaviours and covary with sociodemographic variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…The findings provide additional support to adhering to Idowu et al’s [ 2 ] recommendations regarding the social responsibility in the health sector during a global pandemic. Findings from this study also align with examinations of trust among British individuals during COVID-19 [ 14 ]. Balaet et al examined the relationship between feelings of trust, thoughts about COVID-19, and behaviors.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The findings provide additional support to adhering to Idowu et al’s [ 2 ] recommendations regarding the social responsibility in the health sector during a global pandemic. Findings from this study also align with examinations of trust among British individuals during COVID-19 [ 14 ]. Balaet et al examined the relationship between feelings of trust, thoughts about COVID-19, and behaviors.…”
Section: Discussionsupporting
confidence: 84%
“…Trust is needed to incorporate self-efficacy in the most effective and efficient ways during any stressful situation [9,12]. People's trust in the medical advice and information received from the government about COVID-19 had an impact on the public's compliance with mandated lockdowns and safety recommendations [6,7,[13][14][15][16][17][18]. Without trust, the likelihood of individuals making independent decisions to adhere to safety recommendations, even during a health crisis, is reduced.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This ratio is quite low compared to emergent data from countries such as the United Kingdom where surveys showed 31% of the population did not trust the government to control the spread of the pandemic [53]. Balaet et al further showed that 22% of study participants believed there were "ulterior motives" behind the government's COVID-19 response, with minority populations also tending to show distrust towards the government [54]. For instance, our results are well aligned with a larger study that took place on Twitter, showing that Canada is one of the most trusted countries by its citizens in terms of COVID'19 management (score of 4.1 with 5 representing the highest scoring metric) [55].…”
Section: General Observationsmentioning
confidence: 84%